Adaptación curricular “aprendiendo en movimiento” para fortalecer el aprendizaje en niños y niñas con discapacidad auditiva del instituto de educacion especial Cotopaxi, ubicada en la provincia De Cotopaxi, Canton Latacunga, Barrio Bethlemitas durante el periodo lectivo 2014-2015 - Aguacunchi Segura, Luis Gabriel (2015)
This research has important aspects that will help in order to fortify children’s learning with Hearing Impairment through the application of games and recreational activities which enhance the intellectual, motor, emotional and cultural development. After knowing students’ problem such as the lack of motivation in the teaching-learning development process, has been made clear and achievable objectives. This thesis results from extensive research which has very important aspects in order to the develop an adaptive learning curriculum guide learning in motion, in order to fortify the children’s learning with hearing impairment.